2015
DOI: 10.1038/nrendo.2015.194
|View full text |Cite
|
Sign up to set email alerts
|

The diabetogenic action of statins — mechanisms and clinical implications

Abstract: Treatment with statins has transformed primary and secondary prevention of cardiovascular disease (CVD), including thrombotic stroke. Evidence-based data demonstrate the benefits and safety of statin therapy and help to guide clinicians in the management of populations at high risk of CVD. Nevertheless, clinical trials, meta-analyses and observational studies highlight a 10-12% increase in new-onset diabetes mellitus (NODM) among patients receiving statins. The risk further increases with intensive therapy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
109
0
20

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(146 citation statements)
references
References 106 publications
6
109
0
20
Order By: Relevance
“…Statins, inhibitors of HMG-CoA reductase and well-known cholesterol-lowering drugs, have been used in clinic for almost 40 years and have been proved to be safe, effective drugs with minor side effects. 43, 44, 45 Randomized controlled clinical trials have indicated that statins have provocative and unexpected benefits for reducing the incidence of colorectal cancer and melanoma. 46, 47, 48 Statins can also inhibit tumor growth via different mechanisms, such as inhibition of angiogensis or inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statins, inhibitors of HMG-CoA reductase and well-known cholesterol-lowering drugs, have been used in clinic for almost 40 years and have been proved to be safe, effective drugs with minor side effects. 43, 44, 45 Randomized controlled clinical trials have indicated that statins have provocative and unexpected benefits for reducing the incidence of colorectal cancer and melanoma. 46, 47, 48 Statins can also inhibit tumor growth via different mechanisms, such as inhibition of angiogensis or inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…No evidence shows that statins result in tumor; instead randomized controlled clinical trials indicate that statins have unexpected benefits of reducing tumors. 43-45 …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a study of the HOPS cohort [18] reported a 14% increase in the incidence of DM for each year of statin use, although the authors did not specifically analyze the association between statin dose and DM occurrence. However, as the cardiovascular benefits of high-dose statin use outweigh the potential risk of developing DM [23], it may be advisable to regularly monitor for changes blood glucose and glycated hemoglobin levels in patients who are receiving high-dose statins and have a high risk of developing DM.…”
Section: Discussionmentioning
confidence: 99%
“…109,110 Getting back to the cardiovascular protective effect of statins, a controversy exists due to the observations that statin therapy has been associated with a 10-12% increased risk of developing diabetes. 111 A meta-analysis showed that statin therapy is associated with a 9% increase risk for diabetes; however, authors conclude that the benefits of statin therapy outweighed the risks. 112 Indeed, hyperglycemia produces endothelial dysfunction, a key determinant of diabetic micro-and macro-angiopathy, and statins could be beneficial in both conditions due to pleiotropic effects of this particular class of drugs.…”
Section: Other Potential Epidrugsmentioning
confidence: 99%